2016
DOI: 10.1016/j.chb.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

How employees use Twitter to talk about work: A typology of work-related tweets

Abstract: In organizational research employees' use of personal social media for work remains an understudied phenomenon. Yet, it is important to gain understanding of these online behaviors as they might have consequences on the individual and organizational level. We provide a typology for work-related Twitter use based on a large-scale content analysis (N ¼ 38,124) of tweets sent by 433 employees across different organizations. We found that work-related topics were prevalent in 36.5% of all tweets. Employees' workre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 72 publications
(165 reference statements)
6
100
0
6
Order By: Relevance
“…This measure represents the use of personally owned social media accounts for work‐related communication. The scale is derived from van Zoonen et al ., and was anchored 1 (never) to 7 (very frequently; multiple times a day). Work‐related social media use was measured by asking five questions about the use of Facebook, Twitter and LinkedIn respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This measure represents the use of personally owned social media accounts for work‐related communication. The scale is derived from van Zoonen et al ., and was anchored 1 (never) to 7 (very frequently; multiple times a day). Work‐related social media use was measured by asking five questions about the use of Facebook, Twitter and LinkedIn respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Social media are web‐based services that allow individuals to ‘(1) construct a public or semi‐public profile within a bounded system, (2) articulate a list of other users with whom they share a connection, and (3) view and traverse their list of connections and those made by others within the system’ (Boyd and Ellison, , p. 211), such as Facebook, LinkedIn and Twitter. Although management does not usually prescribe (or, for that matter, proscribe) the use of these personal social media, employees increasingly choose to utilise them for work (McDonald and Thompson, ; van Zoonen et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…This is perhaps surprising as some research on blogging has suggested that this mechanism provides employees with the opportunity to vent about the negative aspects of their jobs, to seek justice, or to distance themselves from corporate culture (Richards, ; Klaas et al ., ; Richards and Kosmala, ). At the same time, this finding is in line with research which shows that social media users are more likely to share content with a positive or neutral rather than negative sentiment (van Zoonen et al ., ) and that negative online utterances tend to be deemed inappropriate and incongruent with self‐views, particularly if the content is related to their professional life (Marwick and Boyd, ). The higher percentage of positive tweets among highly influential users also supports this view.…”
Section: Discussionmentioning
confidence: 99%
“…At present there is limited research exploring how Twitter may be used to voice job satisfaction/dissatisfaction. An analysis of 38,124 tweets of 433 employees in professional jobs (van Zoonen et al ., ) found that approximately a third of these were work‐related and that these referred most frequently to the profession, the organization, work behaviours and in‐group communication. The research by van Zoonen et al .…”
Section: Employee Voice and Job Satisfactionmentioning
confidence: 99%